Effects of cyclo-oxygenase inhibition on exhaled eicosanoids in patients with COPD. Issue 10 (28th September 2005) - Montuschi, P; Macagno, F; Parente, P; Valente, S; Lauriola, L; Ciappi, G; Kharitonov, S A; Barnes, P J; Ciabattoni, G
Abstract : Background: Leukotriene (LT) B4 concentrations are increased and prostaglandin (PG) E2 concentrations are decreased in exhaled breath condensate (EBC) in patients with chronic obstructive pulmonary disease (COPD). A study was undertaken to investigate the short term effects of cyclo-oxygenase (COX) inhibition on exhaled LTB4 and PGE2 concentrations in patients with COPD and to identify the COX isoform responsible for exhaled PGE2 production. Methods: Two studies were performed. A double blind, crossover, randomised, placebo controlled study with ibuprofen (400 mg qid for 2 days), a non-selective COX inhibitor, was undertaken in 14 patients with stable COPD, and an open label study with oral rofecoxib (25 mg once a day for 5 days), a selective COX-2 inhibitor, was undertaken in a different group of 16 COPD patients. EBC was collected before and after drug treatment. Exhaled LTB4 and PGE2 concentrations were measured with specific immunoassays. Results: All patients complied with treatment as indicated by a reduction in ex vivo serum thromboxane B2 concentrations (ibuprofen) and a reduction in lipopolysaccharide induced increase in ex vivo plasma PGE2 values (rofecoxib) of more than 80%. Exhaled LTB4 was increased after ibuprofen (median 175.5 (interquartile range 128.8–231.5) pg/ml v 84.0 (70.0–98.5) pg/ml, p<0.001) and exhaled PGE2 was reduced (93.5 (84.0–105–5) pg/ml v 22.0 (15.0–25.5) pg/ml, p<0.0001). Rofecoxib had no effect on exhaled LTB4 (p = 0.53) or PGE2 (p = 0.23). Conclusions: Non-selective COX inhibition decreases PGE2 and increases LTB4 in EBC, whereas selective COX-2 inhibition has no effect on these eicosanoids. PGE2 in EBC is primarily derived from COX-1 activity, and COX inhibition may redirect arachidonic acid metabolism towards the 5-lipoxygenase pathway.